Economically viable isolation and characterization of oleanolic acid from Eugenia caryophyllus (Spreng.) - Banarase, Nilesh Bhimrao; Kaur, Chanchal Deep (Kuwait Journal of Science, 2020)
Oleanolic acid, an interesting molecule found widespread throughout the plant kingdom with promising pharmacological activities. However, the utilization of oleanolic acid in the modern therapy is quite difficult due to lack of proper isolation method and selection of commercially available raw material. In the present study, the new economic method for the isolation of oleanolic acid from Eugenia caryophyllus (Spreng.) commonly known as clove bud was developed. The yield of oleanolic acid was found to be 1.8 g/ 100 g dry matter. The isolated oleanolic acid was characterized by TLC, DSC, FTIR, ESI-HRMS, and NMR studies. The purity of an isolated oleanolic acid was determined by HPLC studies and found to be 97.7% pure. The method so developed is simple, cost-effective with industrial applicability.